Clinical and biochemical heterogeneity between patients with glycogen storage disease type IA: the added value of CUSUM for metabolic control. Issue 5 (10th April 2017) - Peeks, Fabian; Steunenberg, Thomas A. H.; de Boer, Foekje; Rubio‐Gozalbo, M. Estela; Williams, Monique; Burghard, Rob; Rajas, Fabienne; Oosterveer, Maaike H.; Weinstein, David A.; Derks, Terry G. J.
Abstract: Objective: To study heterogeneity between patients with glycogen storage disease type Ia (GSD Ia), a rare inherited disorder of carbohydrate metabolism caused by the deficiency of glucose‐6‐phosphatase (G6Pase). Study design: Descriptive retrospective study of longitudinal clinical and biochemical data and long‐term complications in 20 GSD Ia patients. We included 11 patients with homozygous G6PC mutations and siblings from four families carrying identical G6PC genotypes. To display subtle variations for repeated triglyceride measurements with respect to time for individual patients, CUSUM‐analysis graphs were constructed. Results: Patients with different homozygous G6PC mutations showed important differences in height, BMI, and biochemical parameters (i.e., lactate, uric acid, triglyceride, and cholesterol concentrations). Furthermore, CUSUM‐analysis predicts and displays subtle changes in longitudinal blood triglyceride concentrations. Siblings in families also displayed important differences in biochemical parameters (i.e., lactate, uric acid, triglycerides, and cholesterol concentrations) and long‐term complications (i.e., liver adenomas, nephropathy, and osteopenia/osteoporosis). Conclusions: Differences between GSD Ia patients reflect large clinical and biochemical heterogeneity. Heterogeneity between GSD Ia patients with homozygous G6PC mutations indicate an important role of the G6PC genotype/mutations. Differences between affected siblings suggest an additional role (genetic and/or environmental) of modifying factors defining the GSD Ia phenotype. CUSUM‐analysis can facilitate single‐patient monitoring of metabolic control and future application of this method may improve precision medicine for patients both with GSD and remaining inherited metabolic diseases.